Citizen consultations on science communication: A citizen science approach - Delicado, Ana (2021)
Citizen science is part of a wider trend in science and society of promoting two-way dialogue and engagement between scientists and the public, by involving citizens in the research process. This paper examines how CONCISE, an international research project involving Spain, Italy, Portugal, Poland, and Slovakia, seeks to understand how citizens acquire and use scientific information, by engaging citizens through public consultations. The consultations gathered close to 500 citizens in 2019. Asking them for suggestions on how to improve science communication and involving them in the dissemination efforts, CONCISE aims to put citizens at the core of the research process.